Componential Skills in Second Language Development of Bilingual Children With Specific Language Impairment. Issue 2 (April 2017) - Verhoeven, Ludo; Steenge, Judit; van Leeuwe, Jan; van Balkom, Hans
Abstract : In this study, we investigated which componential skills can be distinguished in the second language (L2) development of 140 bilingual children with specific language impairment in the Netherlands, aged 6–11 years, divided into 3 age groups. L2 development was assessed by means of spoken language tasks representing different language skills organized into 4 categories based on prior research. Factor analyses were consistent with this system, identifying 4 types of componential skills included in our original assessment battery: (i) speech production/phonological memory; (ii) auditory perception/phonological conceptualization; (iii) lexical-semantic skills; and (iv) morphosyntactic skills. Structural equation modeling showed the 4 types of componential skills to be reasonably stable over time. Moreover, empirical evidence for a lexical bootstrapping effect was found in that children's syntactic development at the age of 8 years could be predicted from their level of lexical-semantic development at the age of 7 years.